Evaluasi Penjualan Produk Gadai Syariah Dan Kepatuhannya Terhadap Prinsip Ekonomi Islam Di Pegadaian Syariah Makassar - Wahyuni, Sinar; jamaluddin, jamaluddin (Institut Agama Islam Tafaqquh Fiddin Dumai, 2024)
The purpose of this study was to determine the sales of Central Sharia Pawnshop Jl. Samalona Makassar and to find out whether product sales are in accordance with the principles of Islamic Economics. This type of research uses qualitative research. The data source this research is primary data obtained directly from the Central Sharia Pawnshop Jl. Samalona Makassar, which is the form of data from the number of customers, turnover, and profits as well as secondary data from library research. Furthermore, the data collection method is carried out by abservation, interviews, and documentation for further analysis by reducing data, presenting data and drawing conclusions. The result of this study indicate that the sale of product used by Central Sharia Pawnshop Jl. Samalona Makassar is inseparable from OJK and DSN regulations. The transaction process is easier and faster so that it can attact custumers to use pawnshop service. It is evident from the number of customers, turnover, and pofit have increased every year